Pengaruh Kinerja Keuangan dan Good Corporate Governance terhadap Nilai Perusahaan melalui Pengungkapan Islamic Sosial Reporting sebagai Variable Moderasi (Studi Empiris Pada Perusahaan yang Terdaftar di JII Pada Tahun 2017-2018) - Alfiatur Rohmaniyah; Aida Nahar (Jurnal Rekognisi Akuntansi, 2019)
The economy in Indonesia is getting better because many entrepreneurs are able to manage their companies well. A good company is a company that has good corporate value. This study aims to analyze the effect of financial performance and corporate governance on firm value and moderated by Islamic Social Reporting on active companies listed in the Jakarta Islamic Index (JII) in 2017-2018 as many as 58 companies. This study uses the dependent variable, namely firm value, the independent variable, namely financial performance and corporate governance and the moderating variable of Islamic Social Reporting. The type of data in this study is quantitative data. This study uses secondary data from the annual reports of active companies published by the Jakarta Islamic Index in 2017-2018. Data analysis used multiple linear regression equation. The results of this study indicate that financial performance has a significant negative effect on firm value, Corporate Governance has a significant negative effect on firm value. Meanwhile, ISR is able to strengthen the relationship between financial performance and firm value and strengthen the relationship between corporate governance and firm value.